Oral Pre-Exposure Prophylaxis (PrEP) for HIV Prevention, Clinical Effectiveness, Safety, Adherence, and Risk Compensation in all Populations - Ibrahim Tomi; Eamon O’Murchu; Liam Marshall; Conor Teljeur; Patricia Harrington; Catherine Hayes; Patrick Moran; Mairin Ryan (STRADA : Jurnal Ilmiah Kesehatan, 2023)
Based on WHO and UNAIDS reports in 2021, 38.4 million (33.9-43.8 million) HIV cases in the world, in Indonesia reported by 34 provinces, the number of people living with HIV found in the January-March 2022 period was 10,525 941,973 people have HIV, and 8,784 people are receiving ARV treatment. The aim of this study is to observe the literature on the clinical efficacy, safety, compliance and risk compliance of oral pre-exposure prophylaxis (PrEP) for HIV prevention in all population groups. A literature review was carried out by identifying national and international articles regarding pre-exposure prophylaxis (PrEP) for preventing HIV transmission. The database used was Google Scholar, Pubmed, Science Direct, The Lancet. There were 331 articles searched from the Pubmed online database, 14 articles, Proquest 134, Science Direct 105, The Lancet 2, Google Scholar 105. There were 20 articles that met the inclusion criteria and were processed.